Temporal trends of environmental toxins –and pesticides from 2003-2014 in the U.S. - NHANES - Kiesewetter, Klaas Robert Hermann; Štěrbová, Ludmila, 1957-; Feigl Ding, Eric; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2017)
In this thesis, the following research questions were reviewed:To what extent have urinary levels of environmental toxins changed within the U.S. population from 2003-2014 and do environmental toxins still pose a threat to public health in the U.S.?Are there any statistically significant associations between environmental pesticides and food products labelled 'organic'?Data were retrieved from the United States National Health and Nutrition Examination Surveys, 2003–2014 including demographics socio-demographics, laboratory data (urinary levels of environmental toxins –and pesticides) and questionnaire data to examine the associations between environmental pesticides and dietary intakes of foods labelled “organic”.Statistical analyses including, geometric mean (GM), 95% confidence interval of geometric mean (CI GM) were performed. Descriptive statistics in form of multiple linear regression models, adjusted for gender and age, in model 1 and race/ethnicity, education level, annual household income, marital status and body-mass-index in model 2, were also performed. Both models were duplicated and adjusted for urinary creatinine (µg/g).Temporal trends for environmental toxins from 2003–2014 were downward and significant overall. Statistically significant (p<0.05) results were obtained for associations of lower urinary 2,5-dichlorophenol and (∑EPM) concentrations (GM) among participants who exclusively bought organic food, compared to participants who completely avoided to buy organic. Further statically significant associations of lower urinary pesticides level according to certain organic food products were obtained. Urinary mean levels of environmental pesticides were generally higher among NHANES participants who haven’t bought/consumed food products, labelled 'organic'.
Vedoucí práce: Ludmila Štěrbová
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2017
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2017
Způsob přístupu: Internet
Keywords: international business - central european business realities [obor dipl. práce]; diplomové práce; master's theses